If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.42857143(m + 5) = 3 + 2m Reorder the terms: -0.42857143(5 + m) = 3 + 2m (5 * -0.42857143 + m * -0.42857143) = 3 + 2m (-2.14285715 + -0.42857143m) = 3 + 2m Solving -2.14285715 + -0.42857143m = 3 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. -2.14285715 + -0.42857143m + -2m = 3 + 2m + -2m Combine like terms: -0.42857143m + -2m = -2.42857143m -2.14285715 + -2.42857143m = 3 + 2m + -2m Combine like terms: 2m + -2m = 0 -2.14285715 + -2.42857143m = 3 + 0 -2.14285715 + -2.42857143m = 3 Add '2.14285715' to each side of the equation. -2.14285715 + 2.14285715 + -2.42857143m = 3 + 2.14285715 Combine like terms: -2.14285715 + 2.14285715 = 0.00000000 0.00000000 + -2.42857143m = 3 + 2.14285715 -2.42857143m = 3 + 2.14285715 Combine like terms: 3 + 2.14285715 = 5.14285715 -2.42857143m = 5.14285715 Divide each side by '-2.42857143'. m = -2.117647061 Simplifying m = -2.117647061
| 18-14xt=80 | | 12x^2-60x-72=0 | | 18-14x=80 | | 7.5y+1.85=-46.90 | | X^2-225x+5=0 | | 2(7+s)=42 | | 1/2(130-x)=45 | | 4(x+2.23)=3x | | 7x-3=74-4x | | (x-1)(x-1)=(x+3)(x-4) | | 6x^2+9=-4x | | 11/3x+1/6-8/3x+9/16 | | 10-3=7 | | 16-11=5 | | 4x-6/3=6 | | 32=0.5(x+42) | | 4=10x-3x^2 | | 4/11x-9+2/11x=18-3/11x | | 1/2((100-y)-y)=40 | | 1/2(100-2x)=40 | | -3x^2+21x-18=0 | | .15x+.05(12-x)=.10(4) | | 11=((8x+7)/3) | | 0.5(x-(180-x))=50 | | 9n+56=7n-2n-4 | | 3x-4y=4+4 | | ((x+7)/14)=1-(3/2)x | | ((6n-5p)/11t)=c | | -7-9y=63 | | -7(7)+9y=-63 | | 184=.56x | | 74=.56x |